Sanitasi Lingkungan Rumah Balita Stunting Di Wilayah Kerja Puskesmas Karang Rejo Metro Utara - Indarwati, Suami; Barus, Linda; Masra, Ferizal (Universitas Malahayati Bandar Lampung, 2023)
Background: Stunting is a disruption in the growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by their length or height being below standard. Stunting conditions can have an impact on the lives of toddlers, both short-term and long-term impacts.Purpose: Understand the risk factors for environmental sanitization of the home of stunting toddler in the Work Area of Puskesmas Karang Rejo Metro Utara.Methods: The research carried out is descriptive in nature, because it describes the risk factors for environmental sanitization of the home of stunting toddler in the Work Area of Puskesmas Karang Rejo Metro Utara in 2023. The population and sampel were all house of stunted toddlers recorded in the Puskesmas Karang Rejo Metro Utara up to August 2022, totaling 31 houses. (Puskesmas Karang Rejo Metro Utara Report 2022). The research was carried out in the Work Area of Puskesmas Karang Rejo Metro Utara in April - August 2023.Results: Of the 31 houses of stunted toddlers based on data from the Puskesmas Karangrejo, researchers only managed to get data for 25 houses. The analysis used in this research is univariate analysis which is used to determine the frequency distribution of the variables studied, and is displayed in the form of a frequency distribution table of respondents based on physical home facilities and home sanitation facilities in the working area of the Puskesmas Karang Rejo Metro Utara, Kota Metro in 2023.Conclusion: In this study, there were 5 stunted toddlers living in houses with physical facilities that met the requirements and 20 stunted toddlers living in houses with physical facilities that did not meet the requirements, and there was 1 stunted toddler living in a house with household sanitation facilities that met the requirements and 24 Stunted toddlers live in houses with household sanitation facilities that do not meet the requirements. Keywords: Stunting, Sanitization, House, Toddler ABSTRAK Latar Belakang: Stunting adalah gangguan pertumbuhan dan perkembangan anak akibat kekurangan gizi kronis dan infeksi berulang, yang ditandai dengan panjang atau tinggi badannya berada di bawah standar. Kondisi stunting dapat memberikan dampak terhadap kehidupan balita, baik dampak jangka pendek maupun jangka panjang.Tujuan: Mengetahui gambaran factor resiko sanitasi lingkungan rumah balita stunting di Wilayah Kerja Puskemas Karang Rejo Metro Utara.Metode: Penelitian yang dilakukan bersifat deskriptif, karena menggambarkan faktor resiko sanitasi lingkungan rumah balita stunting di Wilayah Kerja Puskemas Karang Rejo Metro Utara Tahun 2023. Populasi dan sampel pada penelitian ini adalah seluruh rumah dari balita stunting yang tercatat di Wilayah Puskemas Karang Rejo Metro Utara sampai dengan bulan Agustus tahun 2022 sebanyak 31 buah rumah. (Laporan Puskemas Karang Rejo tahun 2022). Penelitian dilaksanakan di Wilayah kerja Puskemas Karang Rejo Metro Utara pada bulan April - Agustus tahun 2023.Hasil: Dari 31 rumah balita stunting berdasarkan data Puskesmas Karangrejo, peneliti hanya berhasil mendapatkan datanya sebanyak 25 rumah saja. Analisis yang digunakan dalam penelitian ini adalah analisis univariat yang digunakan untuk mengetahui distribusi frekuensi pada variable yang diteliti, dan ditampilkan dalam bentuk tabel distribusi frekuensi responden berdasarkan sarana fisik rumah dan sarana sanitasi rumah di wilayah kerja Puskesmas Karangrejo, kecamatan Metro Utara, Kota Metro tahun 2023.Kesimpulan: Dalam penelitian ini terdapat 5 orang balita stunting mendiami rumah dengan sarana fisik rumah yang memenuhi syarat dan 20 orang balita stunting mendiami rumah dengan sarana fisik rumah yang tidak memenuhi syarat, serta terdapat 1 orang balita stunting mendiami rumah dengan sarana sanitasi rumah yang memenuhi syarat dan 24 orang balita stunting mendiami rumah dengan sarana sanitasi rumah yang tidak memenuhi syarat. Kata Kunci: Stunting, Sanitasi, Rumah, Balita,